The world of biology and politics organization and research areas - Peterson, Steven A.; Somit, Albert (Bingley, U.K. : Emerald, 2013)
This volume describes (a) the present academic and institutional status of Biopolitics and (b) the wide range of research areas that have emerged within the field.The Introduction puts into perspective the major differences and similarities between Biopolitics and more traditional approaches to political science in terms of basic concepts, scope, research methodology, and the resulting implications for public policy. The next two chapters focus on the institutions and organizations that have significantly influenced the structure and direction of the "movement." Chapter 4 describes how and why evolutionary theory has had an increasingly influential impact on political science. Chapters 5 through 9 are "case studies" of how biological perspectives have been productively used in several of the disciplines established "fields." Chapter 10 is a measured critical analysis of the enterprise and Chapter 11 looks at where biopolitics as a field might be moving.
Biology and politics : an introduction / Albert Somit, Steven A. Peterson -- Biology and politics as an organizational enterprise / Albert Somit, Steven A. Peterson -- Graduate education in biology and politics / Milton Lodge ... [et al.] -- On the evolutionary roots of the social sciences / Tatu Vanhanen -- Neuropolitics and political science : providing a foundation for the study of politics / John M. Friend, Bradley A. Thayer -- The biopolitics of the great apes / Johan M.G. van der Dennen -- Biopolicy : can it provide a new paradigm? / Odelia Funke -- Attempted assassination and presidential achievement : the case of Ronald Reagan / Robert E. Gilbert -- Toward an evolutionary synthesis of individualist and communist anarchism : the evolutionary bases of cooperation / Steven A. Peterson -- Success or failure? A critical but optimistic evaluation of biopolitics / Robert H. Blank, Michael Bang Petersen -- The politics of evolutionary theory and biopolitics in the future / Albert Somit, Steven A. Peterson.
Includes index.
Print version record
Keywords: Political Science -- General; Political science & theory; "Biology, life sciences".; Biopolitics